Effects of Government Intervention on SMMEs: A Review of Empirical Evidence - Aluko, Timothy; Bayai, Innocent; Enwereji, Prince (Acta Universitatis Danubius. Œconomica, 2023)
Over the last two decades, governments around the globe have been providing financial and non-financial resources to support small micro and medium-sized enterprises (SMMEs) through grants and subsidies. But, do these public investments aid SMMEs in improving their performance and growth in terms of job creation, productivity, sales, and their ability to survive? The analysis, which focused on government subsidies and grant programmes provides an answer to this question through a review of evidence on the effects of public intervention over the period of 2010 to 2022. Results indicate that government intervention programmes have had a favourable overall impact on business employment creation, sales/turnover, and productivity, with conflicting results for business labour productivity and business survival. Despite the divergent empirical results across programmes, it is imperative for government intervention programmes to address inclusiveness in the designing and implementation phase of grants and subsidies programme, so as to link programme objectives with the intended outcome.